CHANGES IN THE TRENDS IN THE USE OF INFORMATION AND COMMUNICATION TOOLS FOR FUTURE PROFESSIONAL AND TECHNOLOGICAL EDUCATION SPECIALISTS - Юрій Туранов; Володимир Рак; Ірина Луцик; Юрій Франко (Фізико-математична освіта)
Formulation of the problem. The study aims to substantiate and determine the dynamics of changes in the use of information and communication tools in the process of training future specialists in vocational and technological education.